Effects of acupuncture on behavioral, cardiovascular and hormonal responses in restraint-stressed Wistar rats - Guimarães C.M.; Pinge M.C.M.; Yamamura Y.; Mello L.E.A.M. (Brazilian Journal of Medical and Biological Research, 1997)
Stress is a well-known entity and may be defined as a threat to the homeostasis of a being. In the present study, we evaluated the effects of acupuncture on the physiological responses induced by restraint stress. Acupuncture is an ancient therapeutic technique which is used in the treatment and prevention of diseases. Its proposed mechanisms of action are based on the principle of homeostasis. Adult male Wistar EPM-1 rats were divided into four groups: group I (N = 12), unrestrained rats with cannulas previously implanted into their femoral arteries for blood pressure and heart rate measurements; group II (N = 12), rats that were also cannulated and were submitted to 60-min immobilization; group III (N = 12), same as group II but with acupuncture needles implanted at points SP6, S36, REN17, P6 and DU20 during the immobilization period; group IV (N = 14), same as group III but with needles implanted at points not related to acupuncture (non-acupoints). During the 60-min immobilization period animals were assessed for stress-related behaviors, heart rate, blood pressure and plasma corticosterone, noradrenaline and adrenaline levels. Group III animals showed a significant reduction (60% on average, P<0.02) in restraint-induced behaviors when compared to groups II and IV. Data from cardiovascular and hormonal assessments indicated no differences between group III and group II and IV animals, but tended to be lower (50% reduction on average) in group I animals. We hypothesize that acupuncture at points SP6, S36, REN17, P6 and DU20 has an anxiolytic effect on restraint-induced stress that is not due to a sedative action